2003
DOI: 10.1034/j.1600-0420.2003.00038.x
|View full text |Cite
|
Sign up to set email alerts
|

Optic nerve hypoplasia in cholestatic infants: a multiple case study

Abstract: ABSTRACT.Purpose: To present four infants with optic nerve hypoplasia and cholestasis. Methods: All patients underwent detailed ophthalmological and hepatological assessment. Their endocrinological and neuroradiological examinations were re-evaluated. Results: All four infants presented with cholestasis and were subsequently found to have optic nerve hypoplasia. One child was blind according to the WHO definition and two had low vision. The fourth child had unilateral optic nerve hypoplasia and was too young t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Neonatal jaundice was only found in children with ONH (32%), which is in accordance with the 23% reported by Margalith et al (1984). Two of the children with neonatal jaundice developed neonatal cholestasis and have been reported elsewhere (Fahnehjelm et al 2003b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neonatal jaundice was only found in children with ONH (32%), which is in accordance with the 23% reported by Margalith et al (1984). Two of the children with neonatal jaundice developed neonatal cholestasis and have been reported elsewhere (Fahnehjelm et al 2003b).…”
Section: Discussionmentioning
confidence: 99%
“…Details of somatic, neuroradiological and psychological characteristics of the present study group have been reported elsewhere (Fahnehjelm et al 2003a). Six of the patients with ONH have been reported elsewhere (Hellström et al 1999b; Fahnehjelm et al 2003b).…”
Section: Introductionmentioning
confidence: 99%
“…Some of the diseases in the group of metabolic disorders as well as the cardiovascular and chromosomal disorders are known to have malformations related to the disease aetiology regardless of the presence of cholestasis. [76][77][78][79][80][81][82][83][84][85][86][87][88][89][90][91][92][93] The details can be seen in Table 2B and Table S5.…”
Section: Malformationsmentioning
confidence: 99%
“…No ocular manifestations have been reported in association with AATD and PFIC. However, pituitary dysfunction and panhypopituitarism can be associated with optic nerve hypoplasia (ONH) (Fahnehjelm et al. 2003; Karnsakul et al.…”
Section: Introductionmentioning
confidence: 99%